Petrology, tectonic setting, and 40 Ar/ 39Ar (hornblende) dating of the Late Ordovician - Early Silurian Belle Cote Road orthogneiss, western Cape Breton Highlands, Nova Scotia - Price, Joanne; Barr, Sandra; Raeside, Robert; Reynolds, Peter (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1999)
The Belle Cdte Road orthogneiss is a major component of the western Cape Breton Highlands, where it forms a belt approximately 60 km in length. Previous U-Pb dating has shown that the granodioritic to tonalitic protolith of the gneiss crystallized at 442 ♦ 3 Ma, providing a minimum age for the metavolcanic and metasedimentary units of the Aspy terrane intruded by the orthogneiss. The gneissic fabric in the orthogneiss is mainly conformable with the regional fabric, and generally trends north-south, except in the southern part of the unit where it is oriented east-west. Typical orthogneiss contains quartz, plagioclase, and biotite, with variable amounts of K-feldspar and muscovite and rarely epidote or garnet. A tonalitic variant contains amphibole. The orthogneiss is peraluminous, with A/CNK values of I to 1.2. Petrochemical characteristics are consistent with syntectonic emplacement in the roots of a volcanic arc built on continental crust. 40Ar/39Ar dating was done on hornblende from three samples of orthogneiss and seven samples of amphibolite from xenoliths in the orthogneiss and an adjacent amphibolite unit. Eight of these samples yielded cooling ages ranging between 384 and 370 Ma. Two younger ages (ca. 363 and 353 Ma) may reflect localized effects of younger plutonism and/or shearing. The ^Ar/^Ar data combined with previous U-Pb data from titanite indicate that the orthogneiss and associated units experienced rapid cooling from ca. 600 to 400°C between ca. 386 Ma and 370 Ma, perhaps related to uplift associated with ongoing terrane amalgamation in Cape Breton Island.